The effect of intravenous magnesium sulphate infusion on total intravenous anesthesia with propofol in adult dogs: A randomized, blinded trial - Júnior, Gilberto Serighelli; Comassetto, Felipe; Conterno, Gabriela Borges; Victor de Souza, João; de Souza Ferreira, William [UNESP]; Griebeler, Leonardo Bergmann; Oleskovicz, Nilson (Elsevier, 2024)
Objective: To evaluate cardiopulmonary, arterial blood gas and propofol-sparing effects of magnesium sulfate (MgSO4) constant rate infusion (CRI) in mechanically ventilated dogs maintained under total intravenous anesthesia with propofol. Study design: Blinded, randomized, clinical trial. Animals: A total of 24 healthy adult dogs. Methods: Dogs were premedicated with intramuscular acepromazine (0.05 mg kg–1) and morphine (0.5 mg kg–1), followed by an intravenous (IV) bolus of saline or MgSO4 (50 mg kg–1 over 15 minutes) and propofol (given to effect to induce anesthesia). Anesthesia was maintained with an IV propofol infusion (beginning at 0.3 mg kg–1 minute–1, adjusted as necessary). Concurrently, one of three IV infusions were administered: GS (0.9% NaCl), GM30 (MgSO4, 30 mg kg–1 hour–1) or GM80 (MgSO4, 80 mg kg–1 hour–1). Propofol induction and maintenance doses were recorded. The following variables were recorded at baseline (T0), after bolus treatment (T1), after beginning mechanical ventilation (T5) and every 15 minutes until the end of the procedure (T15–T120): mean arterial pressure, heart rate, peripheral oxygen saturation, end-tidal partial pressure of CO2, temperature, blood gas variables, indirect calorimetry and extubation time. Values of p < 0.05 were considered significant. Results: Propofol induction bolus dose was lower in GM30 (31.2%, p = 0.04) and GM80 (38.9%, p = 0.003) than in GS. The maintenance propofol infusion rate in GM80 was 16.9% lower (p = 0.03), resulting in fewer propofol CRI rescues during the perioperative period. GM30 and GM80 exhibited faster extubation times than GS (46.2%, p = 0.002 and 48.9%, p = 0.001, respectively). Conclusions and clinical relevance: Infusion of a 50 mg kg–1 bolus, followed by CRI of MgSO4 (30 and 80 mg kg–1 hour–1), reduces the propofol induction and maintenance (CRI) requirement, maintaining cardiorespiratory stability and reducing the time required to extubation.
Keywords: anesthesia; magnesium sulfate; mechanical ventilation; sedation